Recent Results for the ECHo Experiment - Velte, Clemens; Blaum, Klaus; Goodacre, T. Day; Dorrer, H.; Düllmann, Ch. E.; Eberhardt, K.; Eliseev, S.; Enss, Christian; Filianin, P.; Fäßler, A.; Fleischmann, Andreas; Gastaldo, Loredana; et al. (Journal of low temperature physics, 2016)
The Electron Capture in $$^{163}$$163Ho experiment, ECHo, is designed to investigate the electron neutrino mass in the sub-eV range by means of the analysis of the calorimetrically measured spectrum following the electron capture (EC) in $$^{163}$$163Ho. Arrays of low-temperature metallic magnetic calorimeters (MMCs), read-out by microwave SQUID multiplexing, will be used in this experiment. With a first MMC prototype having the $$^{163}$$163Ho source ion-implanted into the absorber, we performed the first high energy resolution measurement of the EC spectrum, which demonstrated the feasibility of such an experiment. In addition to the technological challenges for the development of MMC arrays, which preserve the single pixel performance in terms of energy resolution and bandwidth, the success of the experiment relies on the availability of large ultra-pure $$^{163}$$163Ho samples, on the precise description of the expected spectrum, and on the identification and reduction of background. We present preliminary results obtained with standard MMCs developed for soft X-ray spectroscopy, maXs-20, where the $$^{163}$$163Ho ion-implantation was performed using a high-purity $$^{163}$$163Ho source produced by advanced chemical and mass separation. With these measurements, we aim at determining an upper limit for the background level due to source contamination and provide a refined description of the calorimetrically measured spectrum. We discuss the plan for a medium scale experiment, ECHo-1k, in which about $$1000\,Bq$$1000Bqof high-purity $$^{163}$$163Ho will be ion-implanted into detector arrays. With one year of measuring time, we will be able to achieve a sensitivity on the electron neutrino mass below 20 eV/c$$^2$$2(90 $$%$$%C.L.), improving the present limit by more than one order of magnitude. This experiment will guide the necessary developments to reach the sub-eV sensitivity.
Gesehen am 30.04.2020